A Halogen‐Free Green High Energy Density Oxidizer from H‐FOX. Issue 20 (9th May 2019) - Dharavath, Srinivas; Tang, Yongxing; Kumar, Dheeraj; Mitchell, Lauren A.; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract : Reaction of H‐FOX (1‐hydrazinyl‐2, 2‐dinitroethenamine) with 2, 2, 2‐trinitroethanol resulted in an unexpected compound, 1, 1′‐methylenebis[3‐(2, 2, 2‐trinitroethyl)urea] (5 ), which when treated with acetic anhydride and 100 % nitric acid gave an N ‐NO2 derivative, 1, 1′‐methylenebis[1‐nitro‐3‐(2, 2, 2‐trinitroethyl)urea] (6 ) in good yield. Compound 6 exhibits a good oxygen balance (+20.4 %), density ( d = 1.87 g/cm 3 ) and excellent detonation performance (vD = 8910 m/s; P = 35.8 GPa) as well as acceptable stability and sensitivity, which suggests it as an attractive replacement for ammonium perchlorate (AP). Abstract : Development of new halogen free green energetic oxidizers 1, 1′‐methylenebis[3‐(2, 2, 2‐trinitroethyl)urea] and 1, 1′‐methylenebis[1‐nitro‐3‐(2, 2, 2‐trinitroethyl)urea] results from sensitive H‐FOX in good yields. Both compounds have high nitrogen and oxygen content and exhibit high densities and good detonation properties.